Development of polymeric seed coats for seed quality enhancement of soybean Glycine max - KUMAR, JITENDER; NISAR, K; ARUN KUMAR, M B; WALIA, SURESH; SHAKIL, N A; PRASAD, RAJENDER (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2004-05 to study the seed quality enhancement of soybean (Glycine max L. Merr.) using polymeric/clay seed coats. Twelve polymers-based and 1 clay-based seed coats were prepared and compared with the commercial formulation of Thiram 75 DS for seed quality enhancement of soybean seed under storage. The carriers employed included acacia, tragacanth, rosin, ethyl cellulose, hydroxy ethyl cellulose, polyethyl methacrylate, methyl cellulose, polyethylene glycol, polyvinyl chloride, polyvinyl acetate, polyvinyl pyrrolidone, and Agrimer VA 6 and the clay bentonite. The polymer-coated seeds in general deteriorated at a slower rate compared with the control and revealed high germination percentage over the control. Apparently the coats acted as barriers to the moisture and checked the deterioration of seed. These also prevented the proliferation of storage fungi over an elevated period. Among all the polymers, polyethy1 methacrylate, polyvinyl acetate and polyvinyl pyrrolidone were found to be significantly superior (P = 0.01) in maintaining the soybean seed quality during storage. On perusal of correlation matrix (germination, vigour and moisture), it was observed that the moisture content of seed revealed significant negative correlation with seed germination (0.8776), seed vigour (0.7240). These products were useful in improving the storability of the seed by checking the fungal infestation and enhancing the overall seed quality during storage